LGBTQIA+ International Students and Socioemotional Well-Being: Impact of Intersectionality on Perceived Experiences and Campus Engagement - Herridge, Andrew Scott; Bodine Al-Sharif, Mary Ann; Leong, Mi Chelle; Garcia, Hugo (Journal of International Students, 2022)
International students are more likely to experience mental health issues and increased stress. Mental health is often surrounded by negative societal stigmas that act as barriers to seeking support and tend to lead to greater mental health concerns. International students tend to seek socioemotional support from other international student peers rather than seeking out counseling services. However, this study shows that LGBTQIA+ international students were less likely to seek socioemotional support from other international student peers due to fear of their sexual orientation being discovered and their families finding out about their identity. This study examines how LGBTQIA+ international students talk about their experiences on and off campus in relations to their socioemotional well-being. Specifically, this study sought to better understand the complexities of LGBTQIA+ students’ identities, and the challenges they faced in terms of their socioemotional well-being. Implications for practice and future research are discussed.